Optimizing Policies for the Distribution of Social Assistance (BANSOS) and Direct Cash Transfers (BLT) to Ensure Targeting Accuracy and Improve Economic Welfare - Subekti, Fiqi Restu; Kensiwi, Noni (Journal Governance Bureaucratic Review, 2025)
Social Assistance (Bansos) and Direct Cash Transfers (BLT) constitute important instruments for poverty alleviation in Indonesia. However, their distribution often encounters targeting errors caused by inaccurate beneficiary data, nontransparent distribution processes, and potential program politicization. These targeting errors generate budgetary inefficiencies and undermine public confidence in the effectiveness of assistance. Consequently, policy reform of Bansos and BLT distribution assumes critical importance. This article aims to identify the primary obstacles in the distribution of Bansos and BLT and to formulate practical strategic policy solutions that enhance targeting accuracy and program effectiveness. The literature review further explores reform measures that can improve benefit distribution and promote more equitable improvements in community economic welfare. The research employs a literature-study approach to analyze policies, official reports, and relevant literature concerning Bansos and BLT distribution. The review covers regulatory frameworks, beneficiary data, and recommendations from academic and policy practitioners. The study recommends several key strategies, including updating beneficiary data using the National Identification Number (NIK); increasing transparency of distribution procedures; establishing independent oversight to prevent program politicization; strengthening digital infrastructure in frontier, outermost, and disadvantaged (3T) regions; implementing a responsive public complaints mechanism; and adopting multidimensional poverty indicators. Implementing the proposed strategic solutions should enhance the effectiveness of Bansos and BLT programs and thereby foster a more equitable and sustainable improvement in the economic welfare of target populations.